Students perception of learning environment: A Base Line Study for identifying areas of concern at a Private Medical College, Bangladesh (Bangladesh Journal of Medical Science, 2016)
Background: The importance of learning environment in teaching institution is increasingly being appreciated in terms of its effect on learning and outcome. Objective: The objective of this study was to explore students perception of learning environment for identifying measures to improve it of a private medical college, Bangladesh. Method: Two phase cross-sectional study combining quantitative and qualitative components was conducted among the students of a private medical college. In Phase I part the Dundee Ready Education Environment Measure (DREEM) inventory was used to obtain data for base line quantitative information on a total of 204 medical and final professional examinee students. Purposive sampling method was employed in this phase and the Item that scored >3 was categorised as highest and < 2 was categorised as lowest scored item. In Phase II part the highest and lowest score items were explored further by qualitative method of focus group discussions among teachers and students on two separate occasions. For focus group discussion a combination of 10 (clinical and preclinical) teachers and 10 students (2x5 =10) except the examinee batch were selected by convenience sampling method. The purpose and method of the focus group was clearly stated to the participants and a consent form was signed by one participant on behalf of the respective group. Results: The response rate was 100% in Phase I part of the study with a perceived global DREEM mean score was 120/200 (22.984) which indicated students positive perception towards the learning environment of ISMC. The global score for year 1, 2, 3, 4, 5 and examinee students were 133/200 (12.959); 134/200 (15.678); 127/200 (9.895); 112/200 (17.205); 67/200 (22.623) and 14/200 (22.984) respectively. The 1st year and 2nd year had highest global score whereas 5th year students had lowest score. The perceived Domains mean scores for Students Perception of Learning (SPoL) was 29.35/48 (8.189); Students Perception of Teacher (SPoT) 27.24/44 (5.195); Students Academic Self Perception (SASP) 18.69/32 (6.726); Students Perception of Atmosphere (SPoA) 28.09/48 (6.844) and Students Social Self Perception (SSSP) 14.65/28 (2.952) which indicated students positive perception in all five Domains of DREEM as well. Out of 50 items three scored >3 and 7 items scored